2005
DOI: 10.1186/bcr1203
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of breast cancer based on gene-expression patterns in peripheral blood cells

Abstract: Introduction Existing methods to detect breast cancer in asymptomatic patients have limitations, and there is a need to develop more accurate and convenient methods. In this study, we investigated whether early detection of breast cancer is possible by analyzing gene-expression patterns in peripheral blood cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 21 publications
5
108
2
Order By: Relevance
“…11,12 Tumour-recruited BMDC are likely to initiate differentiation and effector programs during their mobilisation from the bone marrow, which might be detectable during their transition in the blood. 13,14 The report of signatures derived from peripheral blood mononuclear cells (PBMC) gene expression profiles and associated with breast, 15 renal, 16,17 pulmonary, 18 bladder 19 and digestive cancers 8,9,20 further corroborates these observations. The aim of this study was to demonstrate whether the feasibility of identifying gene expression signatures in PBMC was able to discriminate patients with AP and CRC from subjects without these lesions.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…11,12 Tumour-recruited BMDC are likely to initiate differentiation and effector programs during their mobilisation from the bone marrow, which might be detectable during their transition in the blood. 13,14 The report of signatures derived from peripheral blood mononuclear cells (PBMC) gene expression profiles and associated with breast, 15 renal, 16,17 pulmonary, 18 bladder 19 and digestive cancers 8,9,20 further corroborates these observations. The aim of this study was to demonstrate whether the feasibility of identifying gene expression signatures in PBMC was able to discriminate patients with AP and CRC from subjects without these lesions.…”
Section: Introductionsupporting
confidence: 66%
“…20 Similar results have been reported for other type of tumours, such as breast, bladder, small cell lung cancer and renal carcinoma. [15][16][17][18][19] In particular, different panels of peripheral blood biomarkers based on gene expression have been described in recent studies to differentiate CRC from controls. Han et al identified and validated a five-gene combination that could discriminate CRC from non-CRC samples with sensitivity and specificity of 94% and 77% respectively.…”
mentioning
confidence: 99%
“…28 A study comparing DNA methylation profiles between WBC and EBV-transformed LCL from the same individuals found that the majority of genes have similar 3 H]-methyl acceptance assay and concluded that the two assays had good and DNA methylation status of specific sequences has also been found to be correlated with neutrophil count, suggesting different cell types have alternative ways to regulate expression of their genome. 30 While such evidence supports the presence of differential methylation patterns in different blood cell subsets, it cannot readily explain some of our results, such as why MN DNA methylation correlates so closely with WBC methylation. We might expect that Gran, which represents a larger proportion of cells in the blood (70%), would be more correlated with WBC DNA methylation profile.…”
Section: Discussionmentioning
confidence: 41%
“…This concept has received increasing interest by those examining diverse disorders including autoimmunity, asthma, osteoporosis, Huntington's disease and breast cancer (Borovecki et al 2005, Hakonarson et al 2005, Liu et al 2005, Olsen et al 2004, Sharma et al 2005). Blood is a particularly fitting surrogate for atherosclerotic tissue, because it contains the inflammatory cells such as monocytes that are involved in its pathogenesis (Hansson 2005).…”
Section: Blood As a Tissue Surrogatementioning
confidence: 99%